Haplotypes in the Interleukin 8 Gene and Their Association with Chronic Periodontitis Susceptibility - Scarel-Caminaga, Raquel M. [UNESP]; Kim, Yeon J. [UNESP]; Viana, Aline C. [UNESP]; Curtis, Karen M. C. [UNESP]; Corbi, Samia C. T. [UNESP]; Sogumo, Patricia M. [UNESP]; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP] (Springer/plenum Publishers, 2011)
Interleukin-8 (IL-8), which is responsible for the migration and activation of neutrophils, is an important inflammatory mediator involved in the initiation and amplification of acute inflammatory reactions and chronic inflammatory processes. IL-8 plays an important role in periodontitis, an inflammatory disease characterized by the loss of connective tissue and alveolar bone. The aim of this study was to investigate whether the SNPs rs2227307 (+396) and rs2227306 (+781), and the haplotypes they formed together with the previously investigated rs4073 (-251), were associated with chronic periodontitis susceptibility. Clinical periodontal exams were performed and DNA samples were collected from 493 individuals (223 with periodontitis and 270 controls). Associations between SNPs, haplotypes, and subject phenotypes were analyzed using the chi(2) test followed by multivariate logistic regression modeling. We conclude that the +396TT genotype and the haplotypes ATC/TTC and AGT/TGC were significantly associated with chronic periodontitis susceptibility in Brazilians.
Keywords: Interleukin 8; Periodontitis; Polymorphism; Disease susceptibility